2020
DOI: 10.3390/genes11080918
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of chIFITMs in Avian Coronavirus Infection In Vivo, Ex Vivo and In Vitro

Abstract: The coronaviruses are a large family of enveloped RNA viruses that commonly cause gastrointestinal or respiratory illnesses in the infected host. Avian coronavirus infectious bronchitis virus (IBV) is a highly contagious respiratory pathogen of chickens that can affect the kidneys and reproductive systems resulting in bird mortality and decreased reproductivity. The interferon-inducible transmembrane (IFITM) proteins are activated in response to viral infections and represent a class of cellular restriction fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 87 publications
1
8
0
Order By: Relevance
“…While CEF cells from Aseel took longer to exhibit strong mRNA expression of the chIFN-γ and chIFITM genes, they were strongly expressed at 6 h post-infection. In Kadaknath CEF, among the IR-IFITM family members, chIFITM3 (11.68 log 2 folds) has the greatest expression observed at 6 h post-infection, followed by chIFITM2 (8.89 log 2 folds) at 48 h post-infection, chIFITM1 (7.79 log 2 folds), and chIFITM5 (7.04 log 2 folds) at 24 h post-infection [14,16]. However, in Aseel, IFITM1 (6.00 log 2 folds) came first, then chIFITM3 (3.46 log 2 folds), then chI-FITM2 (3.25 log 2 folds) at 6hpi, and lastly chIFITM5 (3.82 log 2 folds) at 24 hpi.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While CEF cells from Aseel took longer to exhibit strong mRNA expression of the chIFN-γ and chIFITM genes, they were strongly expressed at 6 h post-infection. In Kadaknath CEF, among the IR-IFITM family members, chIFITM3 (11.68 log 2 folds) has the greatest expression observed at 6 h post-infection, followed by chIFITM2 (8.89 log 2 folds) at 48 h post-infection, chIFITM1 (7.79 log 2 folds), and chIFITM5 (7.04 log 2 folds) at 24 h post-infection [14,16]. However, in Aseel, IFITM1 (6.00 log 2 folds) came first, then chIFITM3 (3.46 log 2 folds), then chI-FITM2 (3.25 log 2 folds) at 6hpi, and lastly chIFITM5 (3.82 log 2 folds) at 24 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken has five members of the IFITM family: chIFITM1, chIFITM2, chIFITM3, chIFITM5, and chIFITM10. These protein genes are activated and made to express themselves by type I and type II IFNs, signifying the start of the innate host response in a negative feedback manner [14,33,34]. Recent studies confirm that STAT/IRF signaling pathways activate IFITM gene expression together with other ISGs during infection and inflammation [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tracheal organ culture has long been used to investigate IBV infection [ 106 , 107 , 108 , 109 , 110 , 111 , 112 ]. While this ex vivo model offers many benefits, understanding the mechanisms specifically at the level of tracheal epithelial cells is useful for studying immediate host responses under highly controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic chicks expressing ifitm1 have been demonstrated to restrict H5N1 influenza viruses ( Rohaim et al, 2021 ). Recent studies have demonstrated that infection with IBV will increase the expression of IFITMs in chicks ( Steyn et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%